2011
DOI: 10.1002/jso.21967
|View full text |Cite
|
Sign up to set email alerts
|

Less false‐negative sentinel node procedures in melanoma patients with experience and proper collaboration

Abstract: The sentinel node procedure failed to identify involvement in 5.7% of the patients with lymph node metastases. Half of the false-negative biopsies took place in the first year after the procedure was introduced, illustrating the existence of a learning period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 38 publications
4
35
0
3
Order By: Relevance
“…15,27 In the axilla and groin, however, the reported falsenegative rate is very high and varies between 5.7% and 32.0%, respectively. 24,28 In our study, we were able to demonstrate the reliability and effectiveness of preoperative SPECT/CT imaging for all SLNE without preselection by anatomical site (Table 1 and Figure 2, with an example for cervical, axillary, popliteal, and inguinal SLN). With the SPECT/CT-guided SLNE, we removed more SLNs (2.40 SLNs per patient) than in the standard cohort (1.87 SLNs per patient, PϽ.001), which is consistent with previous studies.…”
Section: Commentmentioning
confidence: 59%
See 1 more Smart Citation
“…15,27 In the axilla and groin, however, the reported falsenegative rate is very high and varies between 5.7% and 32.0%, respectively. 24,28 In our study, we were able to demonstrate the reliability and effectiveness of preoperative SPECT/CT imaging for all SLNE without preselection by anatomical site (Table 1 and Figure 2, with an example for cervical, axillary, popliteal, and inguinal SLN). With the SPECT/CT-guided SLNE, we removed more SLNs (2.40 SLNs per patient) than in the standard cohort (1.87 SLNs per patient, PϽ.001), which is consistent with previous studies.…”
Section: Commentmentioning
confidence: 59%
“…24 The falsenegative rate was defined as the ratio of false-negative results to the total number of positive nodes (falsenegative nodes plus true-positive nodes). 25 …”
Section: False-negative Sentinel Nodementioning
confidence: 99%
“…There is a learning phase for a lymphatic mapping team. A recent study at a specialized melanoma centre showed a 5.7 % false-negative rate over a 15-year period, but the rate was 29.4 % in the first year [66]. Various durations of learning phases have been recommended but none has been based on sound scientific data [67].…”
Section: Procedures Success Rate and Qualifications And Responsibilitmentioning
confidence: 99%
“…SLNB should be performed by a qualified team of nuclear medicine specialists, surgeons and pathologists acting in close collaboration. The success of SLNB continues to increase as a centre gains experience [26,66,68,69].…”
Section: Procedures Success Rate and Qualifications And Responsibilitmentioning
confidence: 99%
See 1 more Smart Citation